Examining the Roles of Government Accounting Officers and Their Implications on Achieving Sustainable Revenue Budget: A Case Study of the Ekiti State Government, Nigeria - Awotomilusi, Niyi; Oso, Oluwayomi; OLUWAGBADE, Oluyinka; Dagunduro, Muyiwa (Journal of Accounting and Finance Management, 2024)
The goal of this study was to uncover the significant impact of government accounting officers' roles on achieving sustainable revenue budgets and to comprehensively investigate how these officers' responsibilities affect the realization of such budgets in Ekiti State. In this research, a survey design was utilized. Data were collected directly from the source by distributing questionnaires to the designated participants, who were the Accounting Officers of the Ekiti State Government. The entire population consisted of 374 accounting officers, and we opted for a census sampling approach, which covers the entire population at 100%. Out of the total questionnaires distributed, 269 were returned with responses. The data collected was subsequently analyzed employing both descriptive and inferential statistical methods. The study found that the roles of accounting officers, specifically pertaining to expenditure control, internal control, and revenue management, have a positive and statistically significant impact on the attainment of a sustainable revenue budget within the Ekiti State Government. It is therefore concluded that when the government exercises strong control over its expenses, it is more likely to achieve its goal of sustaining a balanced and stable budget for the long term. This study recommends that government authorities should recognize the crucial role of accounting officers in achieving fiscal sustainability and provide the necessary support and resources to enable them to fulfill their responsibilities effectively.